WENO Schemes for Mixed-Element Unstructured Meshes (Communications in Computational Physics, 2010)
The paper extends weighted essentially non-oscillatory (WENO) schemes totwo-dimensional quadrilateral and mixed-element unstructured meshes. The key elementof the proposed methods is a reconstruction procedure suitable for arbitrarily-shapedcells. The resulting schemes achieve the designed uniformly high-order ofaccuracy and compute discontinuous solutions without spurious oscillations at interfacesbetween cells of two different types.